(untitled) (Fiep Bulletin - online, 2011)
Often is heard the phrase, "Make a sport to grow," but it is unclear whether this statement is proven scientifically. Whereas most athletes in gymnastics has short stature, it created a myth around that fact. common concern of parents with respect to final height when they observe that their children are smaller than other children the same age (DA SILVA et al., 2004). The assessment of growth was used to target parental height which puts the child up to the parents, so a certain range of height in 95% of children of this couple will reach adulthood, the rate of growth that translates into height gain at a given time interval and BMI to assess nutritional status. Were observed and analyzed the curves away from the variables of stature and body mass index, WHO / WHO (2007). This study is Pre-experimental, with volunteers intentionally selected, a female aged between 8 and 9 years beginning gymnastics artistic practice for over a year of a gym in Barra da Tijuca and a center of initiation Recreational sports in dos Bandeirantes. All patterns are used, finding within the normal range for their ages and levels of growth. Regarding the growth rate, 55% of children met at the range for age, parental target shows that all study subjects should have normal height compared with the standards of Brazilian society, for the Percentiles of the WHO (2007) of height for age 65% of children are in the range of suitable height in relation to BMI for age 70% were located in the eutrophic range. Short stature can then be explained by natural selection dictates the sport, ie, the gymnasts have a short stature because they were selected because they are naturally lower for a lower gymnast is easier to perform exercises body rotation in the air.